Yeast dynamin and Ypt6 function in parallel for the endosome‐to‐Golgi retrieval of Snc1. (16th July 2019) - Makaraci, Pelin; Delgado Cruz, Mariel; McDermott, Hyoeun; Nguyen, Vy; Highfill, Chad; Kim, Kyoungtae
Abstract: Protein recycling is an important cellular process required for cell homeostasis. Results from prior studies have shown that vacuolar sorting protein‐1 (Vps1), a dynamin homolog in yeast, is implicated in protein recycling from the endosome to the trans ‐Golgi Network (TGN). However, the function of Vps1 in relation to Ypt6, a master GTPase in the recycling pathway, remains unknown. The present study reveals that Vps1 physically interacts with Ypt6 if at least one of them is full‐length. We found that overexpression of full‐length Vps1, but not GTP hydrolysis‐defective Vps1 mutants, is sufficient to rescue abnormal phenotypes of Snc1 distribution provoked by the loss of Ypt6, and vice versa. This suggests that Vps1 and Ypt6 function in parallel pathways instead of in a sequential pathway and that GTP binding/hydrolysis of Vps1 is required for proper traffic of Snc1 toward the TGN. Additionally, we identified two novel Vps1‐binding partners, Vti1 and Snc2, which function for the endosome‐derived vesicle fusion at the TGN. Taken together, the present study demonstrates that Vps1 plays a role in later stages of the endosome‐to‐TGN traffic.